2019
DOI: 10.7759/cureus.6467
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lipid Profile in Patients With and Without Acute Myocardial Infarction

Abstract: Introduction There is ample data available to determine the impact of deranged lipid values of acute myocardial infarction (AMI); however, there is a paucity of data from low-income countries like Pakistan. In this study, we aim to determine the correlation of lipid values with AMI. Materials and methods This case-control study was conducted from 1 February 2019 to 30 October 2019 in a tertiary care hospital in Sukkur, Pakistan. There were a total of 421 participants divided into two groups; Case Group (patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Several studies had shown the link between dyslipidaemia and cardiovascular diseases (CVDs). 9,21,22 Stabilising lipid levels in the blood and providing the correct therapy considered an essential key for optimal treatment and a better prognosis for the patients. 23,24 From this point, the urge for understanding and learning guidelines in the healthcare providing system is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had shown the link between dyslipidaemia and cardiovascular diseases (CVDs). 9,21,22 Stabilising lipid levels in the blood and providing the correct therapy considered an essential key for optimal treatment and a better prognosis for the patients. 23,24 From this point, the urge for understanding and learning guidelines in the healthcare providing system is essential.…”
Section: Discussionmentioning
confidence: 99%
“…This study included the samples of 53 MI-positive patients, male and female, and inhibition was checked by a spectrophotometer at 520 nm, which showed 91.73 % inhibition in MI patients. Mal et al compared demographically the lipid profile of two groups in 421 participants, including the patient group (MI patients, n = 212) and the control group (non-MI patients, n = 209) (22). The TC and LDL were remarkably elevated in patients with MI.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may be explained with the modification of the lipid profile that happens early after an acute coronary syndrome (ACS). Almost all researchers agree that after an AMI a phasic fluctuation of the lipid profile may be observed, with a trend that includes reduced total cholesterol, LDL and HDL and increased triglycerides [ 53 ]. These changes generally become manifest within 24–48 h after an acute coronary syndrome, reach a maximum level within approximately 4–7 days and are present for a few months.…”
Section: Discussionmentioning
confidence: 99%